Fe + N Noncompensated Codoping TiO2 Nanowires: The Enhanced Visible Light Photocatalytic Properties - Zhongpo Zhou; Haiying Wang (International Journal of Photoenergy)
The Fe + N codoped nanowire samples are prepared by hydro-thermal method and annealed in NH3 atmosphere. The XRD (X-ray diffraction), SEM (Scanning electron microscope), UV-vis absorption spectroscopy, and BET (Brunauer, Emmett, and Teller) results indicate that the samples are pure anatase nanowires. The Fe + N codoped samples have the highest specific surface area, the largest red-shift, and the largest absorption enhancement in the visible light range compared with Fe doped, N doped, and undoped nanowires. The measurements of XPS (X-ray photoelectron spectroscopy) show that N content of Fe + N codoped TiO2 is about two times as large as that of the N doped TiO2. It is assumed that nitrogen doping plays a very important role for the photocatalytic activity increase and hence the Fe + N codoped nanowire TiO2 shows the most effective photocatalytic activity under the visible light irradiation.